MODEL PENGELOLAAN OBJEK WISATA TIRTA SARI KECAMATAN TILATANG KAMANG BERBASIS MASYARAKAT LOKAL TAHUN 2016-2024 - Safia, Muthia Aini; Fatimah, Siti (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This study examines the management model of the Tirta Sari tourist attraction located in Tilatang Kamang District, Agam Regency, which has been managed independently by the local community from 2016 to 2024. The research is motivated by the suboptimal role of formal institutions in managing the destination, despite its considerable natural and social potential. The purpose of this study is to identify the management structure, service strategies, and the roles of both local residents and migrant communities in supporting the sustainability of the Tirta Sari tourist site. The research applies historical methodology through four stages: heuristics, source criticism, interpretation, and historiography. Data were obtained through interviews, field documentation, and literature review.The findings reveal that the management is collectively carried out by local youth through a daily duty roster system, with division of tasks across operational, infrastructure, external relations, and development sectors. Funding sources include community contributions, donations from migrants, and voluntary visitor support. Key promotional events, such as the Sarasah Sonsang Festival, serve as the main strategies for attracting visitors. Although the management lacks a formal institution such as a Tourism Awareness Group (Pokdarwis), it has succeeded in increasing tourist visits and stimulating the local economy. However, challenges remain, including limited digital promotion, inadequate infrastructure, and minimal government support. This study concludes that a community-based management model can serve as an effective alternative for participatory and sustainable tourism development. Strengthening institutional capacity and fostering cross-sectoral support are essential to enhance the long-term effectiveness of tourism governance in the region.